Vpliv gospodarjenja na biotsko raznovrstnost saproksilnih hroščev - Meterc, Gregor (Gozdarski vestnik, 2015)
In this article we present the impact of some forestry measures (intensity of felling, forest skidding roads) on the chosen saproxylic insects, with the emphasis on NATURA 2000 species, as well as the impact of fires on the sub-cortical fauna of the beetles (some primary saproxylic species). The study of impact of felling intensity and forest roads on the biodiversity of saproxylic beetles was done on the Omphalodo%Fagetum site on three locations (Tolmin, Novo mesto, Postojna) using cross vane funnel traps and pheromone GalloProtect 2D%. The study of the impact of fire was done on 1, 2.5, 3 years old burnt areas in the Sežana area. We found the impact of the intensity of felling in many cases had a positive effect on higher biodiversity of the species from the Cerambycidae family, but biodiversity itself depends heavily on local conditions, especially the amount of dead wood biomass. Biodiversity of sub-cortical entomofauna was the highest on the one year old location; with increasing age of the burnt areas the biodiversity was declining.
Keywords: biodiversity; biotska raznovrstnost; NATURA 2000; gozdarski ukrepi; požarišče; saproksilni hrošči